2016
DOI: 10.1002/2015jf003707
|View full text |Cite
|
Sign up to set email alerts
|

Determining conditions that allow a shear margin to coincide with a Röthlisberger channel

Abstract: The mass loss from the West Antarctic Ice Sheet is dominated by numerous rapidly flowing ice streams, which are separated from stagnant ice in the adjacent ridges by zones of concentrated deformation known as shear margins. Because the discharge from a single ice stream depends sensitively on the ice stream width, determining the physical processes that control shear margin location is crucial to a full understanding of ice stream dynamics. Previous work has shown that the transition from a deforming to an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Moreover, with several margins (e.g., M5B, M5C, and M7B) showing high strain rates but no significant change in basal traction over time, it is unlikely that changes along margins M1A, M3A, M5A, and M7A are merely an artifact of simplified physics in our model. Given that the reported increase in basal drag often occurs along subglacial drainage pathways, we propose that the modeled basal strengthening might be a direct result of hydrological processes associated with efficient hydrology and high basal water fluxes, an interpretation which is consistent with previous work (Platt et al, ; Schroeder et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, with several margins (e.g., M5B, M5C, and M7B) showing high strain rates but no significant change in basal traction over time, it is unlikely that changes along margins M1A, M3A, M5A, and M7A are merely an artifact of simplified physics in our model. Given that the reported increase in basal drag often occurs along subglacial drainage pathways, we propose that the modeled basal strengthening might be a direct result of hydrological processes associated with efficient hydrology and high basal water fluxes, an interpretation which is consistent with previous work (Platt et al, ; Schroeder et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The shear margins that coalesce with basal melt water pathways are almost exclusively situated in the southern sector of PIG, where modeled basal melt rates are high, and the basal hydrological system is inferred to be composed of efficient channels (section ). It is therefore possible that these shear margins formed in unison with a regional hydrological system that now locks them in place, as proposed in recent theoretical work (Elsworth & Suckale, ; Meyer et al, ; Perol et al, ; Platt et al, ). It has been suggested that high deformation rates along shear margins could result in relatively thick layers of temperate ice, which would impede conduction of heat away from the bed and generate high basal melt rates (Beem et al, ; Jacobson & Raymond, ; Perol et al, ; Raymond et al, ; Schoof, ; Suckale et al, ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Both of these processes would lead to subtemperate sliding, that is, sliding at temperatures below the melting point. Additionally, the high stress concentrations may be alleviated by mechanical failure or damage production in the ice itself (Pralong and Funk, 2005).…”
Section: Introductionmentioning
confidence: 99%